Наукова діяльність М.П. Ященка, його роль у розвитку вітчизняного квітникарства та формуванні напрямів досліджень з інтродукції і селекції квітниково-декоративних рослин в Україні - Muzychuk, G.M.; Doroshenko, А.S. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
The analysis on the results of scientific activity, on the background of bright creative biography, of candidate of biological science, one of the famous Ukrainian scientist in the field of introduction and selection of plants for floriculture – Mycola Petrovych Yashchenko have been given as well as the estimation of the main his scientific works and definition of their importance for contemporary and future research.